Sitaru-Schweitzer Type Inequality for Fuzzy and Pseudo-Integrals - Bayaz Daraby; Asghar Rahimi; Mortaza Tahmourasi (Sahand Communications in Mathematical Analysis, 2024)
In this paper, we have proved and stated the Sitaru-Schweitzer type inequality for fuzzy integrals and  also we state this inequality for pseudo-integrals in two classes. The first one is for  pseudo-integrals where pseudo-addition and pseudo-multiplication are constructed by a monotone continuous function $g:[0, \infty ]\to[0, \infty]$. Another one is given by the semiring $([a, b], \max, \odot)$ where an increasing function generates pseudo-multiplication.